If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 4)(4x + 6) = 0 Reorder the terms: (4 + 2x)(4x + 6) = 0 Reorder the terms: (4 + 2x)(6 + 4x) = 0 Multiply (4 + 2x) * (6 + 4x) (4(6 + 4x) + 2x * (6 + 4x)) = 0 ((6 * 4 + 4x * 4) + 2x * (6 + 4x)) = 0 ((24 + 16x) + 2x * (6 + 4x)) = 0 (24 + 16x + (6 * 2x + 4x * 2x)) = 0 (24 + 16x + (12x + 8x2)) = 0 Combine like terms: 16x + 12x = 28x (24 + 28x + 8x2) = 0 Solving 24 + 28x + 8x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(6 + 7x + 2x2) = 0 Factor a trinomial. 4((2 + x)(3 + 2x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Subproblem 2
Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5Solution
x = {-2, -1.5}
| 7x^2-x^2-5=0 | | 9*X+1+3*2X+1=36 | | (10x+5)(4x-6)= | | [1+(2-y)][1-(2-y)]= | | 117-3x=108-4x | | 3(4x-1)=2(6x-5) | | 3(x+5)+2x=20 | | 4xy2/12x | | f(x)=x^3+3x^2-2x-6 | | 3/4(x-4)1/4x=5 | | x=y-42.3 | | x(2a+3b)+x(a+3b)= | | X^2-38x+361=0 | | x(x-4)=x(x)-20 | | 4/5x^2=0 | | x+3+x+x-6=30 | | -5x+24y=200 | | 7-x+4=y | | 9+x-y+3=14 | | x^2-8xy+15y^2+2x-10y=0 | | x=22+6 | | 24+x=55 | | 14-x-8-x=0 | | X+4-3=31 | | X+3*y=15.6 | | 4/√p^3=4p | | X+3*y=31 | | X+3xy=31 | | p^2+7p=q^2+7q | | X/7x4=19 | | 4/√p^3 | | tan^3(x-(1/343) |